2014
DOI: 10.1088/2041-8205/789/1/l10
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Temporal Photon Bunching in Blackbody Radiation

Abstract: Light from thermal black body radiators such as stars exhibits photon bunching behaviour at sufficiently short time-scales. However, with available detector bandwidths, this bunching signal is difficult to be directly used for intensity interferometry with sufficient statistics in astronomy. Here we present an experimental technique to increase the photon bunching signal in blackbody radiation via spectral filtering of the light source. Our measurements reveal strong temporal photon bunching in light from blac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 38 publications
1
36
1
Order By: Relevance
“…3 shows the corresponding experimental results together with the fitting curves based on Eqs. (14) and (16), with only the fiber radius a, the lateral fiber distance d, an additional offset and the visibility as free parameters. As can be seen, the measured g (2) -functions are in excellent agreement with the theoretical expectations.…”
Section: Generation Of Pseudothermal Light Using Multimode Fibersmentioning
confidence: 99%
“…3 shows the corresponding experimental results together with the fitting curves based on Eqs. (14) and (16), with only the fiber radius a, the lateral fiber distance d, an additional offset and the visibility as free parameters. As can be seen, the measured g (2) -functions are in excellent agreement with the theoretical expectations.…”
Section: Generation Of Pseudothermal Light Using Multimode Fibersmentioning
confidence: 99%
“…The pulse length d corresponds to the temporal coherence length of the photon, and recent experiments reported that entangled photons or single photon sources generate photons with the long coherence length of 10 −4 ∼ 10 2 m 43-48 . Although the coherence length of sunlight is approximately several hundreds of nanometers 49 , photons with that of the order of cm are obtained by the spectral filtering technique 50 . The frequency of the pulse ω 0 is set to the localized surface plasmon resonance.…”
Section: Input Two-photon With Correlationmentioning
confidence: 99%
“…The best commercially available thin-film interference band-pass filters typically have transmission bandwidths of a few nanometres, where the transmission bandwidth is defined as the full-width-at-half-maximum (FWHM). In some research fields, in particular quantum optics where it is necessary to distinguish single photons from high background counts at similar wavelengths [1][2][3][4], narrow-band optical filters are required: these filters can have sub-nm transmission bandwidths, while still retaining high on-peak transmission and off-peak extinction. Uses include the demonstration of quantum teleportation [5], quantum memory [6,7] and quantum information processing [8], as well as in other fields of atomic physics such as atom trapping [9].…”
Section: Introductionmentioning
confidence: 99%